On safety, health, productivity and national development (2020)
Occupational health and safety has become an important subject of discourse globally. The aim is to safeguard the safety, comfort and well-being of the workforce of any nation. This is applicable to all branches of industry, business and commerce, information technology establishments, recreational facilities without leaving out domestic activities. As a result of the effect of this subject on the economy and national development together with the challenges involved, the issue has attracted the attention of many stakeholders including government, management of work organisation, researchers among others. In this chapter, the combined impact of safety, health, productivity and national development is conversed. It is concluded that for a nation to develop, productivity must grow steadily and one of the key ways to attain this, is that the health, safety and well-being of the workers who are the drivers of development must be guaranteed in any workplace.